ANALYSIS OF GRAIN’S DRYING IN ATMOSPHERIC DRYER - Shelimanova, E.; Marchuk, B. (Енергетика і автоматика, 2016)
The drying process of wheats’ layer and sunflower seeds in a dryer of atmospheric type is calculated. The paper provides the expediency of such drying technology in climate of Ukraine.